KARAKTERISTIK MUTU DAN CITARASA COKELAT KAYA POLIFENOL - Ramlah, Sitti (Jurnal Industri Hasil Perkebunan, 2016)
Research of Flavor and Quality Characteristics of Rich Polyphenol Chocolate has been done.This research aims to understand the flavor and quality characteristics of polyphenolârich chocolate,therefore can be used for functional food. Research method referred to Ramlah (2014), whereas cocoabeans roasting temperature was set on 40oC and 120oC and re-formulated without soy milk addition.Testing parameters are moisture content, protein as SNI 2323-2008 procedure, fat content as SNI 3749-2009 procedure, flavor test and polyphenol content using spectrophotometer analyzed in IndonesiaCoffee and Cocoa Research Institute, Jember. Results of this study concluded that chocolate madefrom fermented cocoa beans roasted at 40oC has the quality characteristics of the water content of2.03%; protein content of 11.15%; fat content of 48.67% and polyphenol content of 5.36%. Chocolateprepared from fermented cocoa beans roasted at 120oC has the quality characteristics of water contentof 1.43%; protein content of 8.84%; fat content of 53.39% and polyphenol content of 4.83%. In termsof flavor, overall panelistsâ acceptance to chocolate F1 is to have good flavor and aroma and tend to beacidic, whereas chocolate F2 has very good flavor and aroma.Kata Kunci characteristics of quality, flavor, roasting, chocolate, Polyphenol.